Impossibility and gradualism in labor markets: Reflections on the ethics of a living wage - Butner, D. Glenn (Review and expositor, 2019)
Ethicists and economists often raise two objections to the idea of a living wage. The "impossibility objection" claims that raising minimum wages will lead to unemployment. The "gradualism objection" claims that low wages in the present will allow for economic growth and higher wages in the future. This article explores the scriptural warrant for a living wage in light of the impossibility and gradualism objections, arguing that the objections challenge state intervention but not action by specific firms or churches. Paying particular attention to Acts 2:44-45 and 4:32-35, the article challenges churches to consider possible responses to workers' making less than a living wage. Three axes guide Christian business owners and churches in considering responses: a state/local axis, a present/future axis, and a direct/indirect axis. The article concludes by offering concrete policies or ministry proposals along various configurations of the axes.